Behavior of mother to visit posyandu in magetan regency, indonesia - Suharto, Agung; Soedirham, Oedojo; Suparji, Suparji; Hendriyani, Feftin (Open Access Macedonian Journal of Medical Sciences, 2021)
Introduction: The purpose of this study was to develop a model of precede-proceed and social capital influence the improvement of maternal behavior visit to posyandu (the integrated service post). Methods: This study was create model of behavior with cross sectional design. The population was mothers in Magetan and the sample size was 400, selected using simple random sampling. Exogenous variable was social capital, while endogenous variables were predisposing factors, reinforcing factors, enabling factors, and behavior. Statistical analysis was Confirmatory Factor Analysis and Structural Equation Modeling with the program of Amos 18. Phase 2 was non-equivalent control group pretest-posttest. The independent variable was behavioral models, while dependent variable was the behavior of the mother visited posyandu. Statistical analysis was T-Test. Results and analysis: Intervention precede-proceed model of social capital influence the improvement of maternal behavior to visit posyandu (p-value = 0.000). Conclusion: The intervention precede-proceed model and social capital influence the improvement of maternal behavior to visit posyandu.